The Effectiveness of B-FRESH (Blind-Friendly Efficient Smart Hygiene) Media in Improving Oral Hygiene Among Blind Students at SMPLB and SMALB A YPAB Surabaya - Ahsani Taqwim Ridwan Taqwim Ridwan; Isnanto Isnanto; Bambang Hadi Sugito (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Blind children are children with special needs who have abnormalities in the sense of vision that require services, both in terms of education and health specifically. WHO defines as visual acuity in healthy eyes less than 10/200 or visual field less than 10 degrees of fixation. There was a high percentage of oral hygiene in the poor category in blind students aged 12-18 years at SMPLB and SMALB A YPAB Surabaya. The purpose of this study was to determine the effectiveness of using B-FRESH (Blind-Friendly Efficient Smart Hygiene) media on oral hygiene in blind students. This research is an applied research experiment involving 28 samples. The data collection instrument used was a plaque index assessment sheet and a tooth brushing checklist sheet. The data analysis technique used is the Mann-Whitney test. Based on the Mann-Whitney test, the results obtained P (0.001) <0.05. This value indicates H0 is rejected, so there is an effectiveness of using B-FRESH (Blind-Friendly Efficient Smart Hygiene) media on oral hygiene in blind students. The conclusion of the study is that there is an improvement in oral hygiene after being given B-FRESH (Blind-Friendly Efficient Smart Hygiene) media to blind students, namely from poor to moderate. This study has implications for the importance of tooth brushing practices in maintaining oral hygiene in blind students to improve the oral